Nursing of a patient with cervical spondylopathy treated by Traditional Chinese Medicine collapse combined with wax therapy (中药塌渍联合蜡疗治疗1例项痹病患者的护理体会) - LI Yingying (李莹莹); LIU Jiahuan (刘佳环); JIN Chunling (金春伶); YU Wanjun (于婉君); WANG Lisha (王丽莎) (中西医结合护理)
This paper summarizes the nursing experience of a patient with cervical spondylopathy treated by Traditional Chinese Medicine collapse combined with electric wax therapy. Nurses had conducted a comprehensive nursing assessment, followed by dietary guidance and other routine nursing interventions. Based on the syndrome differentiation, the Traditional Chinese Medicine collapse combined with wax therapy was carried out to relieve the pain caused by cervical spondylopathy and improve the patient’s quality of life. (本文总结中药塌渍联合蜡疗治疗1例项痹病患者的护理经验。护理人员在护理评估、饮食干预等常规护理基础上, 通过辨证分析, 采用中药塌渍结合蜡疗干预, 有效缓解项痹病患者的疼痛症状, 提高患者的生活质量。)